Water- and Fat-Soluble Antioxidants in Human Seminal Plasma and Serum of Fertile Males - Lazzarino, Giacomo (Antioxidants (Basel), 2019)
Reactive oxygen species (ROS) are physiologically involved in functions like sperm maturation, capacitation and acrosome reaction, but their excess is involved in male infertility. Antioxidants in seminal plasma (SP) are an important factor balancing physiologic and harmful ROS activities. In this study, we determined and compared the full profiles of the water- and fat-soluble antioxidants in SP and serum of 15 healthy fertile subjects (ranging between the ages of 35 and 42 years). Ejaculates were obtained after 2–5 days of sexual abstinence. After liquefaction and withdrawal of an aliquot for the sperm count, samples were centrifuged to obtain SP. Thirty min after semen donation, a venous blood sample was collected from each subject. Donors with lower SP concentrations of ascorbic acid (n = 5) or α-tocopherol (n = 5) received a 4 week oral administration of either vitamin C (100 mg/day) or vitamin E (30 mg/day). They were then re-assayed to determine the SP and serum levels of ascorbic acid and α-tocopherol. SP and serum samples were properly processed and analyzed by HPLC methods suitable to determine water (ascorbic acid, glutathione (GSH) and uric acid) and fat-soluble (all-trans-retinoic acid, all-trans-retinol, α-tocopherol, carotenoids and coenzyme Q(10)) antioxidants. Data demonstrate that only ascorbic acid is higher in SP than in serum (SP/serum ratio = 4.97 ± 0.88). The other water-soluble antioxidants are equally distributed in the two fluids (GSH SP/serum ratio = 1.14 ± 0.34; uric acid SP/serum ratio = 0.82 ± 0.12). All fat-soluble antioxidants are about 10 times less concentrated in SP than in serum. In donors treated with vitamin C or vitamin E, ascorbic acid and α-tocopherol significantly increased in both fluids. However, the SP/serum ratio of ascorbic acid was 4.15 ± 0.45 before and 3.27 ± 0.39 after treatment, whilst those of α-tocopherol were 0.11 ± 0.03 before and 0.10 ± 0.02 after treatment. The results of this study, by showing the peculiar composition in water- and fat-soluble antioxidants SP, indicate that it is likely that still-unknown mechanisms allow ascorbic acid accumulation in SP against a concentration gradient. SP mainly relies its defenses on water- rather than fat-soluble antioxidants and on the mechanisms ensuring their transfer from serum.